Efficacy of intravenous immunoglobulin (IVIg) on COVID-19-related neurological disorders over the last 2 years: an up-to-date narrative review - Manganotti, Paolo; Garascia, Gabriele; Furlanis, Giovanni; Buoite Stella, Alex (Frontiers in Neuroscience, 2023)
Introduction: Among the clinical manifestations of SARS-CoV-2 infection, neurological features have been commonly reported and the state-of-the-art suggest several mechanisms of action providing a pathophysiological rationale for central and peripheral neurological systems involvement. However, during the first months of the pandemic, clinicians have challenged to find the best therapeutic options to treat COVID-19 related neurological conditions. Methods: We explored the medical available indexed literature in order to answer the question IVIg could be included as a valid weapon in the therapeutic arsenal against COVID-19 induced neurological disorders. Results: Virtually all reviewed studies were in agreement in detecting an acceptable to great efficacy for IVIg employment in neurological diseases, with no or mild adverse effects. In the first part of this narrative review, the interaction of SARS-CoV-2 with the nervous system has been discussed, and IVIg mechanisms of action reviewed. In the second part of the review we collected data from the scientific literature of the last two years to discuss the use of IVIg therapy in different Neuro-COVID conditions, providing a summary of the treatment strategies and key findings. Discussion: Intravenous immunoglobulins (IVIg) therapy is a versatile tool with multiple molecular targets and mechanisms of action, which might respond to some of the suggested effects of the infection, as the inflammatory and autoimmune responses. As such, IVIg therapy has been used in several COVID-19 related neurological diseases, including polyneuropathies, encephalitis, and status epilepticus, and results have often shown improvement of symptoms, suggesting IVIg treatment to be safe and effective.